Regulation of Subscription-based Video Streaming Over-The-Top platforms in Brazil: A proposal based on the enforced self-regulation model - Azevedo, Carlos Henrique Almeida José e (Law, State and Telecommunications Review, 2020)
Purpose ”“ This paper proposes an enforced self-regulation model for the regulation of video streaming OTT services in Brazil. The proposed model seeks to presents itself as an alternative to the existing regulatory asymmetry in which Cable TV and its similar are regulated through Law no. 12,485 while Video Streaming OTT services are provided to the public without any regulatory burden. Methodology ”“ Through a literature review of the Responsive Regulation Theory, this paper presents a proposed model to the regulation of Video Streaming OTT platforms in Brazil based on the enforced self-regulation model as described by Ayres and Braithwaite. Findings ”“ Considering the Brazilian legal environment and the successful use of negotional legal tools, an enforced self-regulation model for Video Streaming OTTs arises as a feasible alternative for the current regulatory asymmetry between such services and Cable TV. Originality ”“ In an unprecedented manner in Brazil, this paper proposes an enforced self-regulation model as an alternative to the regulation of video streaming OTT services in Brazil. The relevance of such research lays upon the notorious success of such platforms in the Brazilian market and upon the current worldwide debate on the regulation of OTT services.